Sistem Pakar untuk Mengidentifikasi Kepribadian Siswa Menggunakan Metode Certainty Factor dalam Mendukung Pendekatan Guru - Nadya Andhika Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Not a few teachers who do not understand the personality of students, in the process of teaching some teachers who do not understand the personality of students then the teacher will be difficult to deliver learning materials that will attract students who impact the knowledge transfer process becomes inhibited. From the problems that have been described previously it is necessary an expert system that can replace an expert in the field of psychology to identify the student's personality. Expert System in this study using Certainty Factor method in representing the knowledge gained. The application design from Expert System itself is designed with web-based, because with web-based applications can help the process of dissemination of information and knowledge with a wider area of ​​distribution. Keywords: Expert System, Certainty Factor, Personality